MCSE/MCSA guide to installing and managing Microsoft Winfows XP Professional and Windows Server 2003 - Simpson, Ted (Thomson Course Technology, 2006)
This full-color book combines Course Technology's proven Microsoft Windows Server 2003 and Windows XP Professional content in one volume for those who teach these two popular subjects in a single course.